2005
DOI: 10.1007/s15010-005-8202-2
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Quantification of Antibacterial Effects of Beta-Lactams, Macrolides, and Quinolones against Gram-Positive and Gram-Negative RTI Pathogens

Abstract: Traditionally, the in vitro activity of antibacterial agents is characterized by their minimal inhibitory concentrations. However, these endpoints are, by nature, discrete and do not provide information on time-dependent killing of the bacteria during the incubation period. Nevertheless, the pharmacodynamic characteristics of antibacterial agents are almost always defined by correlating a static endpoint describing the antibacterial activity of an agent with the pharmacokinetics, describing the time-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
3
9
0
2
Order By: Relevance
“…This disconnect between MICs and kill rates is very well in agreement with previously published data [8,20,[40][41][42][43][44][45][46][47]. Wouldn't it be more conclusive to derive PD measures not from static but from dynamic endpoints like kill-rates [65]? In summary, it can be concluded that diverse methods affect discrete static or dynamic endpoints differently.…”
Section: Discussionsupporting
confidence: 89%
“…This disconnect between MICs and kill rates is very well in agreement with previously published data [8,20,[40][41][42][43][44][45][46][47]. Wouldn't it be more conclusive to derive PD measures not from static but from dynamic endpoints like kill-rates [65]? In summary, it can be concluded that diverse methods affect discrete static or dynamic endpoints differently.…”
Section: Discussionsupporting
confidence: 89%
“…1 is the most parsimonious model that was fitted to the observed data. It is similar to previously published models (2,10,13,16,18,20,22), but the basic structure of the model is most similar to the net effect model (2). Comparisons of the different mathematical models showed that potency estimates produced by the various mathematical models were similar (analysis not shown).…”
Section: Discussionsupporting
confidence: 81%
“…The low MRSA-selective potential of moxifloxacin in contrast to the high selective potential of ciprofloxacin and levofloxacin is likely due to the high and pronounced bactericidal activity of moxifloxacin against MSSA and MRSA, whereas ciprofloxacin and levofloxacin reduce viable counts of S. aureus much more slowly as described in this study and as published previously [17,[38][39][40].…”
Section: Discussionsupporting
confidence: 73%